Tác động của thực thi trách nhiệm xã hội của doanh nghiệp đối với sự ưa thích thương hiệu trong ngành nước giải khát của khách hàng trẻ Việt - Hoàng Cửu , Long; Lê Thanh , Trúc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This research analyzes the relationship between Corporate Social Responsibility (CSR) implementation with environment, society, stakeholders; and brand preference. To examine the relationship, research model is provided with hypothesis and tested with more than 168 questionnaires collected from young consumers in the beverage industry in Ho Chi Minh City. The results show that the implementation of CSR influences on brand preference. This also shows that brand quality plays an important part in strengthening the relationship between CSR implementation and brand priority. Brands can be more attractive to young Vietnamese consumers if they are involved in CSR implementation initiatives. This research findings further reinforce that young shoppers in Vietnam are starting to use CSR implementation data to evaluate their preferred brands.